Investigating the pharmacokinetics of a grape seed-derived proanthocyanidin extract in healthy human subjects. - Abdulla, Zohra Bibi (Stellenbosch : Stellenbosch University, 2025)
Thesis (MSc)--Stellenbosch University, 2024.